Photopic and scotopic spatiotemporal tuning of adult zebrafish vision - Hollbach, Nadine; Tappeiner, Christoph; Jazwinska, Anna; Enzmann, Volker; Tschopp, Markus (Frontiers in Systems Neuroscience, 2015)
Sensitivity to spatial and temporal patterns is a fundamental aspect of vision. Herein, we investigated this sensitivity in adult zebrafish for a wide range of spatial (0.014 to 0.511 cycles/degree [c/d]) and temporal frequencies (0.025 to 6 cycles/second) to better understand their visual system. Measurements were performed at photopic (1.8 log cd m-2) and scotopic (-4.5 log cd m-2) light levels to assess the optokinetic response. The resulting spatiotemporal contrast sensitivity functions revealed that the optokinetic response of zebrafish is tuned to spatial frequency and speed but not to temporal frequencies. Thereby, optimal test parameters for contrast sensitivity measurements were identified. At photopic light levels, a spatial frequency of 0.116 ± 0.01 c/d (mean ± SD) and a grating speed of 8.42 ± 2.15 degrees/second (d/s) was ideal; at scotopic light levels, these values were 0.110 ± 0.02 c/d and 5.45 ± 1.31 d/s, respectively. This study allows to better characterize zebrafish mutants with altered vision and to distinguish between defects of rod and cone photoreceptors as measurements were performed under different light conditions.